2019
DOI: 10.5603/gp.2019.0040
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A (SEMA3A), protocadherin 9 (PCdh9), and S100 calcium binding protein A3 (S100A3) as potential biomarkers of carcinogenesis and chemoresistance of different neoplasms, including ovarian cancer — review of literature

Abstract: Ovarian cancer is the fifth leading cause of cancer-related deaths in women. Its high mortality rate results from lack of adequate and sensitive methods allowing for the detection of the early stages of the disease, as well as low efficiency of the treatment, caused by the cytotoxic drug resistance of cancer cells. Unfortunately, tumours are able to develop new pathways and protective mechanisms that allow them to survive toxic conditions of chemotherapy. Therefore, intensive search for new genes and proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…SEMA3A is a member of the semaphorin family of proteins that play a role in many developmental processes as well as in cancer progression [89]. It is a tumor suppressor gene, and its downregulation correlates with progression of gastric [90] and ovarian cancer [91].…”
Section: Discussionmentioning
confidence: 99%
“…SEMA3A is a member of the semaphorin family of proteins that play a role in many developmental processes as well as in cancer progression [89]. It is a tumor suppressor gene, and its downregulation correlates with progression of gastric [90] and ovarian cancer [91].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, among others, S100A3, S100A10, and S100B were identified to be related to drug resistance in ovarian cancer [146][147][148]. Elevated expression of S100A3 was found primarily in ovarian cancer cells resistant to cisplatin and paclitaxel, both standard chemotherapeutic drugs, as well as topotecan, a chemotherapeutic agent commonly used in second-line treatment [146]. S100A10 was 1 of 11 genes associated with multidrug resistance in ovarian primary serous carcinoma tissue, although further studies are needed to validate these data, as this relation could not be confirmed in a group with a smaller sample size [147].…”
Section: S100 Proteins In Ovarian Cancermentioning
confidence: 99%
“…SEMA3s and their receptors have been reported to be related with drug responses in a number of cancer types [3,[59][60][61]. We next investigated the expression of NRPs and PLXNs in NCI-60 cell lines and systematically tested the correlation between their expression levels with drug sensitivity score of over 200 chemotherapy drugs.…”
Section: Neuropilins and Plexins Are Associated With Tumor Stemness Amentioning
confidence: 99%